The Making of the Champions: A Case Study of the Development of The Young Aerobic Gymnasts In Malay, Aklan - Valencia, Mike Jhun Detaro; Maming, Jimmy Bernabe; Medina, Jesalem Hermosa; Macasarte, Glenvee Dagohoy (Future Science / FSH-PH Publications, 2021)
The Philippines has the potential to excel in this field because an athlete's height is not a requirement compared to other sports like swimming, basketball, and the likes. This is qualitative research specifically employs a single case study to explore the narratives of the young aerobic gymnasts in the Municipality of Malay, Aklan. This study utilizes online interviews, observation, and data reviews in gathering the data while Yin's (2003) approached was utilized in the analysis of data. Themes emerged from stories of the participants like Personal Skills and Motivations of Young Aerobic Gymnasts is Foundational in Winning the Competition, Present DepEd Curriculum Lacks Content in Aerobic Gymnastics and Parents, School, Government, and Business Sector Support are Significant Factors for a Gymnast to Succeed. The output of the study is a proposed new Model of Young Aerobic Gymnastics Development